Screening of Novel Antimicrobial Diastereomers of Azithromycin-Thiosemicarbazone Conjugates: A Combined LC-SPE/Cryo NMR, MS/MS and Molecular Modeling Approach - Iva Habinovec; Ivana Mikulandra; Paula Pranjić; Saša Kazazić; Hana Čipčić Paljetak; Antun Barišić; Branimir Bertoša; Mirjana Bukvić; Predrag Novak (MDPI AG, 2022)
A well-known class of antibacterials, 14- and 15-membered macrolides are widely prescribed to treat upper and lower respiratory tract infections. Azithromycin is a 15-membered macrolide antibiotic possessing a broad spectrum of antibacterial potency and favorable pharmacokinetics. Bacterial resistance to marketed antibiotics is growing rapidly and represents one of the major global hazards to human health. Today, there is a high need for discovery of new anti-infective agents to combat resistance. Recently discovered conjugates of azithromycin and thiosemicarbazones, the macrozones, represent one such class that exhibits promising activities against resistant pathogens. In this paper, we employed an approach which combined LC-SPE/cryo NMR, MS/MS and molecular modeling for rapid separation, identification and characterization of bioactive macrozones and their diastereomers. Multitrapping of the chromatographic peaks on SPE cartridges enabled sufficient sample quantities for structure elucidation and biological testing. Furthermore, two-dimensional NOESY NMR data and molecular dynamics simulations revealed stereogenic centers with inversion of chirality. Differences in biological activities among diastereomers were detected. These results should be considered in the process of designing new macrolide compounds with bioactivity. We have shown that this methodology can be used for a fast screening and identification of the macrolide reaction components, including stereoisomers, which can serve as a source of new antibacterials.